Radio spots with agroclimatic information from the Local Technical Agroclimatic Committees for the ASO 2022 climate forecast (Spanish) - Hernández Quevedo, Mónica; Navarro Racines, Carlos Eduardo (2022)
Climate information produced and disseminated through the Local Technical Agroclimatic Committees (MTAs) are shared via radio in 17 departments.